Knowledge, attitude, and practice toward interstitial lung disease among patients: a cross-sectional study - Xu, Wenjie; Li, Qiuhong; Mao, Yanjun; He, Yan (Frontiers in Medicine, 2024)
Objective: To explore the knowledge, attitude, and practice (KAP) toward interstitial lung disease (ILD) among patients and analyze the factors affecting KAP. Methods: This cross-sectional study enrolled patients with ILD treated at the Respiratory Department of Shanghai Pulmonary Hospital between January 2023 and June 2023. A self-administered questionnaire was developed to evaluate their KAP toward ILD through convenient sampling. Multivariate regression analysis and structural equation model (SEM) were used to analyze the factors influencing KAP and their interactions. Results: A total of 397 patients were enrolled, with 61.71% male. The mean KAP scores were 4.60±3.10 (possible range: 0-12), 16.97±2.16 (possible range: 5-25), and 32.60±7.16 (possible range: 9-45), respectively. Multivariate logistic regression analysis showed that junior high school [OR=2.003, 95%CI: 1.056-3.798, P=0.033], high school and above [OR=2.629, 95%CI: 1.315-5.258, P=0.006], and duration of disease ≥5 years [OR=1.857, 95%CI: 1.132-3.046, P=0.014] were independently associated with adequate knowledge. The knowledge [OR=1.108, 95%CI: 1.032-1.189, P=0.005] and duration of disease ≥5 years [OR=0.525, 95%CI: 0.317-0.869, P=0.012] were independently associated with a positive attitude. The knowledge [OR=1.116, 95%CI: 1.036-1.202, P=0.004], attitude [OR=1.180, 95%CI: 1.061-1.312, P=0.002], and the age of >70 years [OR=0.447, 95%CI: 0.245-0.817, P=0.009] were independently associated with the proactive practice. SEM showed that patients’ knowledge of ILD directly affected their attitude (β=0.842, P<0.001) and practice (β=0.363, P<0.001), and their attitude also affected their practice (β=0.347, P=0.014). Conclusion: Patients with ILD in China had poor knowledge, intermediate attitude, and proactive practice toward ILD, which suggests that the health education of patients should be further strengthened.